PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI DALAM BIDANG PENGADAAN TANAH - aan saputra; I Made Sepud; Simon Nahak (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2017)
State official who commit corruption in the Procurement of land for the development in the public interest resulting state losses, must be responsible for what they have done. How the settlement of the corruption in the procurement of land? and how the responsibility from the perpetrators especially in bali ?. Kind of this research is Normative legal research. The results of this study can be concluded by (1) Completion of responsibility For Corruptors in the Court, (2) Responsibility of the Corruptors in the Procurenet of land in Bali, based on Fautes Personalles Theory, which the losses incured charged to local authorities themselves. Key Words : Crime Responsibility, Corruption, Procurrement of Land